Techno-Economic Assessment of Syngas Generation from Municipal Solid Waste in Pakistan: A Simulated Study - Nawaz, H. A.; Abbas, Q.; Ramzan, N.; Naveed, S. (The Nucleus, 2021)
The key objective of this work is to analyze the techno-economic feasibility of municipal solid waste (MSW) gasification plant in a small village named Nano Dogar near Lahore, Pakistan. Sampling of MSW was performed in the village indicating feed rate as 83.4kg/hr equivalent to 2 tons/day. The technical assessment was achieved by using process simulator; ASPEN PLUS version 8.1, in terms of material and energy balance. The results attained were associated with equations finding process efficiency, power generation potential, capital and operating costs. For economic appraisal, various cost parameters were taken into account like interest rate, plant life, operating hours, costs of labor, maintenance, supervision and purchase equipment costs (PEC) to estimate the project feasibility indicators like return on investment (ROI), discounted payback period (DPBP), net present value (NPV), internal rate of return (IRR), and profitability index (PI). This hypothetic gasification plant has power generation potential of 0.175 MW/ton when operated at 800°C and 1 atm, with flowrates of MSW, air and steam as 80 kg/hr, 115 kg/hr and 52 kg/hr at 1 atm, respectively. However, the temperature for MSW and air was 25°C and for steam, it was 200°C. ROI and DPBP were found to be 4.6% and 3 years, respectively. NPV was positive followed by 17% IRR and PI was greater than one. This assessment can be useful to study the technical and economic aspects of gasification plant irrespective of feedstock type such as coal, oil and biomass, and plant capacity.